A Load Scheduling Algorithm for the Smart Home Using Customer Preferences and Real Time Residential Prices. Issue 30 (2015) - Suryanarayanan, Siddharth; Devadass, Marvin Antony; Hansen, Timothy M.
Abstract: A load scheduling method in the Smart Home using a combination of customer preferences and the price of electricity is presented. To translate the customer preference of loads into a time-varying priority curve, the Analytical Hierarchy Process (AHP) and Piecewise Cubic Hermite Interpolating Polynomial (PCHIP) methods are used. The resulting curves of customer priority are combined with the available time-varying pricing information for determining the schedule for each load. An example with four loads is presented to demonstrate the effectiveness of the algorithm.